The Investigation of Psychometric Properties (Validity and Reliability Reassessment) of WHO QOL-BREF Questionnaire in Shahrekord Cohort Study - Fatemeh Salehi; Ali Ahmadi (Shahrekord University of Medical Sciences, 2019)
Background and aims: The purpose of this study was to revalidate the Persian version of the WHO quality of life (WHOQOL-BREF) instrument to determine the quality of life status in the Shahrekord Cohort Study (SCS) in the southwest of Iran. This study was designed to serve as one of the sources of the Prospective Epidemiological Research Studies in Iran. Materials and Methods: In this cross-sectional study, 2000 people were randomly selected from the study population of the SCS. The reliability and internal consistency of the WHOQOL-BREF were measured using Cronbach alpha coefficient and Pearson's correlation. construct validity and factors measured using Pearson's correlation matrices with each of its domains. To measure the face, content, and construct validities, the views of the panel of experts and exploratory factor analysis were used. In addition, the validity of the questionnaire was evaluated using linear regression. Results: All domains of the questionnaire met the minimum reliability standards (Cronbach alpha and intra-class correlation >0.7), except for social relationships. The results of comparison analysis indicated that the questionnaire discriminated well between subgroups of the study samples differing in their health status. Regarding validity, the Kaiser-Meyer-Olkin (KMO) value was 0.94 and the value of Bartlett's test was 1699.01 (P≤0.001). Conclusion: The findings suggested that WHOQOL-BREF is a reliable and valid measure of healthrelated quality of life among SCS population.